Assessing Instructional Cognitive Load in the Context of Students' Psychological Challenge and Threat Orientations: A Multi-Level Latent Profile Analysis of Students and Classrooms - Martin, Andrew J.; Ginns, Paul; Burns, Emma C.; Kennett, Roger; Munro-Smith, Vera; Collie, Rebecca J.; Pearson, Joel (Frontiers in Psychology, 2021)
To better understand instructional cognitive load, it is important to operationalize and assess it in novel ways that can reveal how different students perceive and experience this load. Adopting a within- and between-network construct validity approach, the present study administered a recently developed instruction assessment tool—the Load Reduction Instruction Scale-Short (LRIS-S)—to N = 2,071 students in 188 high school science classrooms. Multilevel latent profile analysis (LPA) was used to identify student and classroom profiles based on students’ reports of instructional cognitive load (load reduction instruction, LRI; using the LRIS-S) and their accompanying psychological challenge orientations (self-efficacy and growth goals), and psychological threat orientations (anxiety and failure avoidance goals). In phase 1 of analyses (investigating students; Level 1), we identified 5 instructional-psychological student profiles that represented different presentations of instructional load, challenge orientation, and threat orientation: Instructionally-Overburdened & Psychologically-Resigned students (9% of students), Instructionally-Burdened & Psychologically-Fearful students (31%), Instructionally-Supported & Psychologically-Composed students (30%), Instructionally-Optimized & Psychologically-Self-Assured students (9%), and Instructionally-Supported & Psychologically-Pressured students (21%). In turn, these profiles (and their component scores) were validated through their significant associations with persistence, disengagement, and achievement—with the Instructionally-Overburdened & Psychologically-Resigned students demonstrating the most maladaptive outcomes and the Instructionally-Optimized & Psychologically-Self-Assured students demonstrating the most adaptive outcomes. In phase 2 of analyses (investigating students and classrooms; Levels 1 and 2), we identified 3 instructional-psychological classroom profiles that varied in instructional cognitive load, challenge orientations, and threat orientations: Striving classrooms (19% of classrooms), Thriving classrooms (31%), and Struggling classrooms (50%). These three classroom profiles (and their component scores) were also validated through their significant associations with classroom-average persistence, disengagement, and achievement—with Struggling classrooms reflecting the most maladaptive outcomes and Thriving classrooms reflecting the most adaptive outcomes (but, notably, equal to Striving classrooms in achievement). Taken together, findings show that considering instructional cognitive load (and new approaches to empirically assessing it) in the context of students’ accompanying psychological orientations can reveal unique insights about students’ learning experiences and about important differences between classrooms in terms of the instructional load that is present.